Application of nanotechnology in the agro-food sector - Lopes, Carla Martins (2020)
Nanotechnology is an emerging field of research that has been widely applied in different scientific and engineering areas. The agro-food sector is not an exception, which considers its applicability in several areas of major interest for both consumers and producers. This review considers major concepts related to nanostructures and nano-based instruments used in the food sector, as well as their applications in agro-food products. Food safety through the use of nanosensors for pathogen detection, smart packaging, and valorisation of food products by nanoencapsulation/nanodelivery of food ingredients (e.g. flavours) are examples of important areas of nanotechnology. Consumers' apprehension regarding food stability and safety issues is also considered.